Effects of Converting Tacrolimus Formulation from Twice-Daily to Once-Daily in Liver Transplantation Recipients - Thorat, Ashok (Hindawi Publishing Corporation, 2014)
Typically, tacrolimus is administrated twice daily. Prolonged-release tacrolimus is the once-daily formulation and may be more convenient for patients. Experience with the administration of the once-daily formulation is still limited. This study enrolled 210 liver transplant recipients who had stable liver function and converted tacrolimus from a twice-daily to once-daily formulation on a 1 mg to 1 mg basis. Among 210 patients, seven patients (3.3%) were withdrawn from the once-daily formulation due to allergy and fatigue. For the other patients, the trough concentration after converting to the once-daily formulation was lower than that of the twice-daily formulation. Liver enzymes were mildly elevated in 3 months after formulation conversion and serum creatinine and uric acid were mildly decreased. Seven patients (3.4%) had clinical suspicion of acute rejection after the formulation conversion and three of them were caused by nonadherence. 155 patients (76.4%) experienced a more convenient life with an increase of social activity. Forty-seven patients (23.2%) experienced the convenience of once-daily formulation during overseas trips. In conclusion, tacrolimus can be safely converted from the twice-daily to the once-daily formulation for most stable liver recipients. Acute rejection may occur in a minority of patients during formulation conversion and should be carefully monitored.